Antimicrobial Prescribing and Stewardship, 1st Volume (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Antimicrobial Prescribing and Stewardship Issue (volume 1) consist of manuscripts, including original research, review articles, case series, and opinion papers for topics related to antimicrobial (antibiotic, antifungal) stewardship, including: Disease-based/organism-based antimicrobial stewardship;Diagnostic stewardship;Influence of antimicrobial utilisation changes in antimicrobial resistance;Impact of antimicrobial stewardship on quality performance measures and patient outcomes;Novel antimicrobial stewardship education and training approaches or interventions aimed at the public and/or healthcare workers;Behavioural change approaches to antimicrobial stewardship;Collaborative practice agreements in antimicrobial stewardship;Antimicrobial stewardship in special populations (e.g., paediatrics, geriatrics, emergency medicine, hematology/oncology);Tackling AMR through antimicrobial stewardship in low- and middle-income countries;Antimicrobial stewardship for animal health;Antimicrobial stewardship in alternative settings (e.g., community practice, long-term care, and resource-limited small and rural hospitals);Antimicrobial use and stewardship in the context of the COVID-19 pandemic;Global collaborations to tackle AMR through antimicrobial stewardship.